Disturbances of visual perception in non-demented patients with Parkinson’s disease - Timofejavaitė , R.; Vilda , V.; Liveikienė , A.; Kaladytė-Lokominienė, R. (Neurologijos seminarai, 2019)
Background. Parkinson’s disease (PD) is a neurodegenerative disease associated with a wide spectrum of non-motor symptoms, including visual hallucinations. Disturbances of visual perception are usually considered to be a complication of PD progression predicting a probability of psychosis or coexisting dementia. Visual hallucinations have multifactorial etiology and are associated with lower visual acuity, long duration of the disease, cognitive disturbances, impaired contrast sensitivity, colour discrimination, and dopaminergic medications. There is limited data on hallucinations in PD without dementia, considering them mostly iatrogenic. Materials and methods. The permission to perform the study was received at Vilnius University Hospital Santaros Klinikos (VUHSK). 30 self-contained patients of VUHSK with PD without dementia staged 1.0-3.0 according to Hoehn and Yahr scale (19 males and 11 females) were interviewed. The control group consisted of 30 subjects (15 males and 15 females) without neurodegenerative diseases and dementia. All participants were evaluated by means of a specially designed questionnaire on disturbances of visual perception, Montreal Cognitive Assessment (MoCA), and Hospital Anxiety and Depression scale (HAD). Clinical data included the burden of PD according to Unified Parkinson’s Disease Rating Scale (UPDRS), the duration of PD, and currently used medications. The dose of dopaminergic medications was converted to Levodopa Equivalent Dose (LED). Patients underwent ophthalmological examination which provided data on colour discrimination, contrast sensitivity, eye pressure, and retinal ganglion cell layer thickness (RGCL). The relations between minor hallucinations and clinical factors were investigated by comparison of PD and control groups, and PD group. Results. 30% of PD patients and 10% of control subjects experienced disturbances of visual perception (p=0.05). The most common visual hallucinations among non-demented patients with PD were kinetopsia and passage hallucinations, more rare – misidentification of objects and macropsia; controls named only passage hallucinations. 6.6% of PD patients named more than one type of minor hallucinations. Hallucinations occurred in 20% of PD patients with unilateral motor symptoms, 20% of patients with bilateral motor disease without postural instability, and 50% of subjects with postural instability caused by progression of PD. The difference of MoCA total score (p=0.006), language (p=0.0026) and executive function (p=0.0004) scores between the groups was statistically significant. 40% of PD patients and 10% of controls were diagnosed with mild cognitive impairment (p=0.015). 30% of PD patients and 10% of control subjects scored 7 points or above in HAD anxiety subscale (p=0.021). The possible link between disturbances of visual perception and UPDRS Mentation, Behavior and Mood subscore (p=0.05), Activities of Daily Living subscore (p=0.064), and RGCL thickness of the left eye (p=0.056) was determined. ROC analysis revealed the highest sensitivity and specificity in visual hallucinations of MoCA score (AUC=0.694; p=0.005), HAD anxiety subscore (AUC=0.697; p=0.013), and UPDRS Activities of Daily Living (ADL) subscore (AUC=0.704; p=0.030). The logistic regression did not reveal significant relations between disturbances of visual perception and age, PD duration and stage, HAD depression subscore, LED, UPDRS total, motor and complications scores, motor lateralisaton, impaired colour discrimination, contrast sensitivity, eye pressure, and visual acuity. Conclusions. Non-demented PD patients experienced disturbances of visual perception probably more frequently than control subjects. These disturbances developed more frequently in case of postural instability. Mild cognitive impairment, disorders of language and executive function were diagnosed more frequently in PD group. Minor hallucinatory phenomena were probably related to thinner RGCL of the left eye and worse UPDRS scores in parts Mentation, Behavior and Mood, and ADL. We recommend that examination of PD patients for disturbances of visual perception include MoCA, HAD anxiety, and UPDRS ADL subscales. A larger sample study is required to obtain re- sults of higher significance.